Assessment Of Risk Factors Associated With Mortality And Developing Drug Resistant Tuberculosis In Hospital Pulau Pinang, Malaysia: A Retrospective Study - Yaghi, Aseel Rezeq Ali (2023)
Globally, Malaysia classified as an intermediate tuberculosis (TB) burden country. Increasing mortality rate and the emergence of multidrug-resistant TB (MDR-TB) played the major role in achieving unsuccessful treatment outcomes among TB patients. Despite the national efforts to control TB in the country, but little is known about the management and treatment outcomes of MDR-TB patients from Malaysia as well as the risk factors of mortality among TB population. For this purpose, a total of 351 TB patients, including 26 MDR-TB patients treated at chest clinic of Hospital Pulau Pinang were included in the present retrospective study. Medical records of TB patients were reviewed and sociodemographic, clinical and microbiological characteristics of the patients were extracted to data collection sheet designed by a team of doctors, pharmacists and health providers. Multivariable logistic and Cox regression were performed using SPSS version 23.